Single atom modification (O-->S) of tRNA confers ribosome binding. - Ashraf, S S (1999)
Escherichia coli tRNALysSUU, as well as human tRNALys3SUU, has 2-thiouridine derivatives at wobble position 34 (s2U*34). Unlike the native tRNALysSUU, the full-length, unmodified transcript of human tRNALys3UUU and the unmodified tRNALys3UUU anticodon stem/loop (ASLLys3UUU) did not bind AAA- or AAG-programmed ribosomes. In contrast, the completely unmodified yeast tRNAPhe anticodon stem/loop (ASLPheGAA) had an affinity (Kd = 136+/-49 nM) similar to that of native yeast tRNAPheGmAA (Kd = 103+/-19 nM). We have found that the single, site-specific substitution of s2U34 for U34 to produce the modified ASLLysSUU was sufficient to restore ribosomal binding. The modified ASLLysSUU bound the ribosome with an affinity (Kd = 176+/-62 nM) comparable to that of native tRNALysSUU (Kd = 70+/-7 nM). Furthermore, in binding to the ribosome, the modified ASLLys3SUU produced the same 16S P-site tRNA footprint as did native E. coli tRNALysSUU, yeast tRNAPheGmAA, and the unmodified ASLPheGAA. The unmodified ASLLys3UUU had no footprint at all. Investigations of thermal stability and structure monitored by UV spectroscopy and NMR showed that the dynamic conformation of the loop of modified ASLLys3SUU was different from that of the unmodified ASLLysUUU, whereas the stems were isomorphous. Based on these and other data, we conclude that s2U34 in tRNALysSUU and in other s2U34-containing tRNAs is critical for generating an anticodon conformation that leads to effective codon interaction in all organisms. This is the first example of a single atom substitution (U34-->s2U34) that confers the property of ribosomal binding on an otherwise inactive tRNA.